For good measure : the ways we say how much, how far, how heavy, how big, how old - Robbins, Ken. (New York : Flash Point, 2010)
Photographs and text explain the meanings and origins of terms related to measurement, such as pounds, miles, and quarts.
"A Neal Porter book"--T.p.
Book Links (A.L.A.)
School Library Journal
Wilson's Children
Book Links (A.L.A.), June 2010
Horn Book, October 2010
Keywords: Weights and measures -- Juvenile literature; Weights and measures; Weights and measures